Enhancement of performance of farmed buffaloes pasture management and feed supplementation in Sabah, Malaysia - Saad, Mohd Zamri; Kasim, Azhar; Abu Bakar @ Zakaria, Md Zuki; Abdullah, Punimin; Abu Hassim, Hasliza (Universiti Putra Malaysia Press, 2017)
A buffalo-breeding farm run on an extensive grazing system without feed supplementation was selected for this study. Farm records between 2004 and 2011 were analysed for selected parameters, particularly calving rate, calving interval, average daily gain of calves and calf mortality. Following the analysis, interventions were implemented in January 2012, which included increase in pasture area from 399 to 441 acres followed by application of organic fertiliser. The selected breeder buffaloes were prepared for breeding by supplementing palm kernel cake-based feed at the rate of 1.5 kg/animal/day for two weeks before breeder males were introduced at the rate of one male to 20 females. Weaning age was reduced from six to three months. Prior to the intervention, proximate analysis of pasture revealed 7.6% crude protein content; approximately 79% of breeder buffaloes were found with a body score of >3; the average annual calving rate was 22%; the calving interval was 24±11.2 months; average daily gain of calves was 0.89±0.21 kg; the average birth weight was 28.31±3.26 kg; and calf mortality was 26.8±7.0%. Following intervention, proximate analysis of grass revealed 12% crude protein content. With feed supplementation, the percentage of breeder females with a body score of >3 increased to 95%, leading to an average annual calving rate of 50%. Average birth weight was significantly (p<0.05) improved to 35.4±5.39 kg, while the average daily gain was 0.95±0.32 kg. Subsequently, the average calving interval was reduced to 15.2±9.2 months. Similarly, calf mortality rate was significantly (p<0.05) reduced to 17.6±4.7%. In conclusion, improved management, particularly of pasture and feeding, significantly enhanced the performance of farmed buffaloes.